Innovative Pharmacological Therapies for the Hemophilias Not Based on Deficient Factor Replacement - Mannucci, Pier Mannuccio; Mancuso, Maria Elisa; Santagostino, Elena; Franchini, Massimo (Seminars in Thrombosis and Hemostasis, 2016)
In recent years, advances in the pharmacological treatment of hemophilias A and B have mainly focused on the development of long-acting factor (F)VIII and FIX products. Alternative approaches not based on the replacement of the missing factor have also been explored, with the aim of producing therapeutic agents with reduced immunogenicity and yet equally effective in patients with or without inhibitors. These new classes of hemostatic agents act mainly by bypassing the need of FVIII and FIX in tenase formation, quenching anticoagulant pathways, enhancing the activity of some coagulation factors or stabilizing the fibrin clot. Current knowledge on the status of development of these novel molecules is summarized in this narrative review. We also surmise that the main interests for these products not based on the replacement of FVIII or FIX in deficient patients pertain to the potential for bleeding prevention in inhibitor patients, an earlier and easier prophylaxis implementation thanks to subcutaneous administration and prolonged half-life, and a low immunogenicity with the potential for prevention of inhibitor development in high-risk patients.
Keywords: hemostatic agents; ACE910; concizumab; antithrombin; FV variant; FX variant